Serum vibriocidal responses when second doses of oral cholera vaccine are delayed 6 months in Zambia. Issue 32 (22nd July 2021) - Mwaba, John; Chisenga, Caroline Cleopatra; Xiao, Shaoming; Ng'ombe, Harriet; Banda, Elena; Shea, Patrick; Mabula-Bwalya, Chileshe; Mwila-Kazimbaya, Katayi; Laban, Natasha Makabilo; Alabi, Peter; Chirwa-Chobe, Masuzyo; Simuyandi, Michelo; et al.
Abstract: Two-dose killed oral cholera vaccines (OCV) are currently being used widely to control cholera. The standard dose-interval for OCV is 2 weeks; however, during emergency use of the vaccine, it may be more appropriate to use the available doses to quickly give a single dose to more people and give a delayed second dose when more vaccine becomes available. This study is an open label, randomized, phase 2 clinical trial of the vibriocidal response induced by OCV, comparing the responses when the second dose was given either 2 weeks (standard dose interval) or 6 months (extended dose interval) after the first dose. Vaccine was administered to healthy participants > 1 year of age living in the Lukanga Swamps area of Zambia. Three age cohorts (<5 years, 5–14 years, and ≥ 15 years) were randomized to the either dose-interval. The primary outcome was the vibriocidal GMT 14 days after the second dose. 156 of 172 subjects enrolled in the study were included in this analysis. The Inaba vibriocidal titers were not significantly different 14 days post dose two for a standard dose-interval GMT: 45.6 (32–64.9), as compared to the GMT 47.6 (32.6–69.3), for the extended dose-interval, (p = 0.87). However, the Ogawa vibriocidal GMTs were significantly higher 14 days post dose two for the extended-dose interval at 87.6 (58.9–130.4) compared to the standard dose-interval group at 49.7 (34.1–72.3), p = 0.04. Vibriocidal seroconversion rates (a > 4-fold rise in vibriocidal titer) were not significantly different between dose-interval groups. This study demonstrated that vibriocidal titers 14 days after a second dose when given at an extended\ dose interval were similar to the standard dose-interval. The findings suggest that a flexible dosing schedule may be considered when epidemiologically appropriate. The trial was registered at Clinical Trials.gov (NCT03373669).